Plastic litter in streams: The behavioral archaeology of a pervasive environmental problem. (July 2017) - Carpenter, Evan; Wolverton, Steve
Abstract: Plastic deposition in hydrological systems is a pervasive problem at all geographic scales from loci of pollution to global ocean circulation. Much attention has been devoted to plastic deposition in marine contexts, but little is known about inputs of plastics into local hydrological systems, such as streams. Attempts to prevent plastic litter must incorporate the role of people's behaviors, so we employ a behavioral archaeological framework to distinguish between various cultural inputs (e.g., littering) and noncultural forces (e.g., stream transport and wind) that affect litter patterns on the landscape. Four sites with varying cultural uses were surveyed monthly for eight months along a creek in Texas, and analysis of the data included chi-square and Kruskal Wallis tests, and abundance indices comparing material types across sites. We found that sites have drastically different distributions in plastic litter, and these patterns appear to align with the cultural uses (hiking, fishing, roadway) and presence or absence of noncultural forces at each site. This information can be used to inform efforts to reduce littering at these and potentially other locations with similar characteristics. This study illustrates that an archaeological framework provides an efficient and accurate way to generate local data on littering behaviors. Highlights: An archaeological framework is used to identify behaviors from litter patterns. Both cultural and environmental factors shape the distribution of litter at a site. Identifying these factors helps in crafting recommendations to reduce litter.